Menentukan Posisi Pengeboran Untuk Mendapatkan Air Yang Berkualitas Di Jalan Tunjung I Denpasar Barat Dengan Metode Geolistrik - Suardika, I Kadek; Simpen, I Nengah; Redana, I Wayan (BULETIN FISIKA, 2017)
Investigation has been conducted on drilling point position to get clean water at Jalan Tunjung 1 Denpasar Barat. The investigation was carried out by geoelectric method using the Wenner configuration. The measurement data is processed by using Res2dev Software. From the resistivity data processing results obtained that the best position to get quality water is at position 8º33'43,76 "LS and 115º21'00,06" BT. The position of the aquifer lies at a depth of 16.25 meters. Laboratory test results for several parameters relating to water quality show values that meet the quality standard threshold in accordance with the provisions of Bali's Governor Regulation no. 8 Year 2007.